Chestnut inner shell extract inhibits viral entry of porcine epidemic diarrhea virus and other coronaviruses in vitro - Kim, Jinman; Jo, Sohee; Choi, Yeojin; Kim, Tae-Won; Park, Jung-Eun (Frontiers in Veterinary Science, 2022)
Porcine epidemic diarrhea virus (PEDV) is a coronavirus that causes acute diarrhea in suckling piglets. Although vaccines are able to reduce the incidence of PEDV infection, outbreaks of PEDV continue to be reported worldwide and cause serious economic losses in the swine industry. To identify novel antiviral sources, we identified the chestnut (Castanea crenata) inner shell (CIS) as a natural material with activity against PEDV infection in vitro. The ethanol fractions of CIS extracts potently inhibited PEDV infection with an IC90 of 30 µg/mL. Further investigation of the virus lifecycle demonstrated that CIS extract particularly targeted the early stages of PEDV infection by blocking viral attachment and membrane fusion at rates of 80~90%. In addition, CIS extract addition reduced the viral entry of other members of the Coronaviridae family. Our data demonstrated that CIS extract inhibited PEDV infection by blocking cell entry in vitro and suggest that CIS extract is a new prophylactic and therapeutic agent against PEDV and other coronavirus infections.